The Effect of NaOH Concentration and Fatty Acid Type on the Physical Properties of Solid Soap in Saponification Reaction Material - Erbaningsih, Erbaningsih; Muna*, Laili Nailul; Hidayah, Muhamad Aditya (Universitas Syiah Kuala, 2025)
The merdeka curriculum in chemistry includes saponification reactions as part of the lipid material, which can be studied through simple experiments such as soap production. This study aims to analyze the effect of NaOH concentration variations and different types of fatty acids in oils (palm oil, olive oil, and corn oil) on the quality of solid soap produced. Additionally, this research explores the utilization of soap-making as a learning resource for understanding the saponification reaction. The research method used is qualitative descriptive with an experimental approach. Analysis was carried out through organoleptic tests, pH tests, and foam height tests. The research method uses a qualitative descriptive method which describes the results of research data and experimental methods for making soap. Based on the study results, in the soap-making process, a good NaOH content is found at a concentration of 30% as indicated by the test results of yellow soap with a melon aroma, solid texture, pH 10, and an average foam height of 5.84 cm. Meanwhile, in soap with variations in fatty acid types, the formulation that produces good quality soap is in F1 with test results of white melon aroma, and solid texture, with an average pH of 10 and an average foam height of 5.50 cm. Based on the results of the soap-making test, the soap-making process can be used as a learning resource for students to understand saponification material. This is by the flow of learning objectives obtained through analysis of the merdeka curriculum manuscript